A review on the development and properties of continuous fiber/epoxy/aluminum hybrid composites for aircraft structures - Botelho,Edson Cocchieri (2006)
Weight reduction and improved damage tolerance characteristics were the prime drivers to develop new family of materials for the aerospace/aeronautical industry. Aiming this objective, a new lightweight Fiber/Metal Laminate (FML) has been developed. The combination of metal and polymer composite laminates can create a synergistic effect on many properties. The mechanical properties of FML shows improvements over the properties of both aluminum alloys and composite materials individually. Due to their excellent properties, FML are being used as fuselage skin structures of the next generation commercial aircrafts. One of the advantages of FML when compared with conventional carbon fiber/epoxy composites is the low moisture absorption. The moisture absorption in FML composites is slower when compared with polymer composites, even under the relatively harsh conditions, due to the barrier of the aluminum outer layers. Due to this favorable atmosphere, recently big companies such as EMBRAER, Aerospatiale, Boing, Airbus, and so one, starting to work with this kind of materials as an alternative to save money and to guarantee the security of their aircrafts.